2019
DOI: 10.1016/j.jviromet.2019.113679
|View full text |Cite
|
Sign up to set email alerts
|

Development of a recombinase polymerase amplification assay with lateral flow dipstick for rapid detection of feline parvovirus

Abstract: Feline panleukopenia caused by feline parvovirus (FPV), a single-stranded DNA virus, is typically highly contagious and often presents with lethal syndrome. The broad spectrum of possible hosts suggests its potential for transmission from animal to person through close contact with pets. FPV thus serves as an example of the importance of new rapid point-of-care field diagnostic tools for the control and prevention of transmission, especially among rare wild animals and pet cats. Recombinase polymerase amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Since there is no need to link the antibody and the oligonucleotide, the operation steps are simplified, and the versatility and convenience of this method are significantly higher than that of I-NAA. Currently, common NAA-I techniques include PCR-LFIA, RPA-LFIA, , LAMP-LFIA, and so on have been widely used in the field of testing.…”
Section: Immunoassay and Nucleic Acid Amplification Combined Technolo...mentioning
confidence: 99%
“…Since there is no need to link the antibody and the oligonucleotide, the operation steps are simplified, and the versatility and convenience of this method are significantly higher than that of I-NAA. Currently, common NAA-I techniques include PCR-LFIA, RPA-LFIA, , LAMP-LFIA, and so on have been widely used in the field of testing.…”
Section: Immunoassay and Nucleic Acid Amplification Combined Technolo...mentioning
confidence: 99%
“…Products of DNA amplification can be detected by a lateral flow dipstick (LFD), which makes the endpoint analysis more flexible and useable in low-resource settings (Crannell et al, 2014;Rostron et al, 2019;Hu et al, 2020;Lei et al, 2020). In previous studies, RPA combined with LFD (LFD-RPA) was found to save time and achieve high sensitivity, high specificity, and convenience, and visual detection of some diseases can be employed (Rosser et al, 2015;Poulton and Webster, 2018;Wang et al, 2019;Shelite et al, 2021). Sun et al set up the LFD-RPA method targeting SjR2 of S. japonicum to diagnose human S. japonicum infection by detecting faecal samples (Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The RPA assay has the advantages of rapidity, speci city, and sensitivity, and doesn't need expensive instruments [5,6]. After the RPA assay, lateral ow dipstick (LFD) could be used to detect the products of DNA ampli cation [7]. Recently, RPA assay coupled with LFD assay (RPA-LFD) has been reported to have a good potential in the detection of many pathogens, such as bovine ephemeral fever virus, African swine fever virus, and avian in uenza A virus [8][9][10].…”
Section: Introductionmentioning
confidence: 99%